TNF-α-Secreting Lung Tumor-Infiltrated Monocytes Play a Pivotal Role During Anti-PD-L1 Immunotherapy - De Ridder, Kirsten; Locy, Hanne; Piccioni, Elisa; Zuazo, Miren Ibarra; Awad, Robin Maximilian; Verhulst, Stefaan; Van Bulck, Mathias; De Vlaeminck, Yannick; Lecocq, Quentin; Reijmen, Eva; De Mey, Wout; De Beck, Lien; et al. (Frontiers in Immunology, 2022)
Immune checkpoint blockade (ICB) of the PD-1 pathway revolutionized the survival forecast for advanced non-small cell lung cancer (NSCLC). Yet, the majority of PD-L1+ NSCLC patients are refractory to anti-PD-L1 therapy. Recent observations indicate a pivotal role for the PD-L1+ tumor-infiltrating myeloid cells in therapy failure. As the latter comprise a heterogenous population in the lung tumor microenvironment, we applied an orthotopic Lewis Lung Carcinoma (LLC) model to evaluate 11 different tumor-residing myeloid subsets in response to anti-PD-L1 therapy. While we observed significantly reduced fractions of tumor-infiltrating MHC-IIlow macrophages and monocytes, serological levels of TNF-α restored in lung tumor-bearing mice. Notably, we demonstrated in vivo and in vitro that anti-PD-L1 therapy mediated a monocyte-specific production of, and response to TNF-α, further accompanied by their significant upregulation of CD80, VISTA, LAG-3, SIRP-α and TIM-3. Nevertheless, co-blockade of PD-L1 and TNF-α did not reduce LLC tumor growth. A phenomenon that was partly explained by the observation that monocytes and TNF-α play a Janus-faced role in anti-PD-L1 therapy-mediated CTL stimulation. This was endorsed by the observation that monocytes appeared crucial to effectively boost T cell-mediated LLC killing in vitro upon combined PD-L1 with LAG-3 or SIRP-α blockade. Hence, this study enlightens the biomarker potential of lung tumor-infiltrated monocytes to define more effective ICB combination strategies.